2020
DOI: 10.1097/inf.0000000000002739
|View full text |Cite
|
Sign up to set email alerts
|

Children Hospitalized With Severe COVID-19 in Wuhan

Abstract: Background: Novel coronavirus disease (COVID-19) is spreading globally. Little is known about the risk factors for the clinical outcomes of COVID-19 in children. Methods: A retrospective case-control study was taken in children with severe acute respiratory syndrome coronary virus-2 infection in Wuhan Children’s Hospital. Risk factors associated with the development of COVID-19 and progression were collected and analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(91 citation statements)
references
References 9 publications
5
82
0
4
Order By: Relevance
“…To address this postulation, our further meta-analysis depicted remarkably raised circulating IL-10 levels in severe COVID-19 patients compared with non-severe COVID-19 patients. Our main finding from this meta-analysis may help clarify the inconclusive results derived from several observational studies unveiling that circulating IL-10 levels were higher in severe cases than that in non-severe cases, but the difference is not statistically significant [ 12 , 14 , 15 , 17 , 22 , 24 ]. As regards IL-10 levels relevant to mortality, when 2 previous studies were considered, a study by Huang et al [ 28 ] evinced no statistically significant difference in circulating IL-10 levels between non-survivors and survivors.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…To address this postulation, our further meta-analysis depicted remarkably raised circulating IL-10 levels in severe COVID-19 patients compared with non-severe COVID-19 patients. Our main finding from this meta-analysis may help clarify the inconclusive results derived from several observational studies unveiling that circulating IL-10 levels were higher in severe cases than that in non-severe cases, but the difference is not statistically significant [ 12 , 14 , 15 , 17 , 22 , 24 ]. As regards IL-10 levels relevant to mortality, when 2 previous studies were considered, a study by Huang et al [ 28 ] evinced no statistically significant difference in circulating IL-10 levels between non-survivors and survivors.…”
Section: Discussionmentioning
confidence: 84%
“…Besides IL-6, IL-10 is synthesized from regulatory T cells and even TH 1 cells and has been reportedly implicated in immunoregulation and inflammation [ 9 ], thereby highlighting the power of IL-10 to influence immune and inflammatory responses in the context of COVID-19. Indeed, a number of clinical studies have unveiled that circulating IL-6 levels were elevated in COVID-19 patients, particularly in those with severe stage and were positively associated with the severity and mortality of COVID-19 [ 10 33 ], commensurate with circulating levels of IL-10 and TNF-α [ 12 , 14 , 15 , 17 , 18 , 20 , 21 , 24 , 28 , 29 ]. Based on these previous findings, alterations in circulating levels of IL-6, IL-10, and TNF-α have been hypothesized to be biomarkers of disease severity and mortality for COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…60 Hepatic enzyme alterations in SARS-CoV-2-positive patients are also common and have been associated with the severity of the infection. 48,[61][62][63][64] Although CRP and IL-6 levels have been associated with higher mortality rates and severity of disease, 65 reports in the literature are contradictory. Some studies have reported no difference in the elevation of proinflammatory biomarkers between patients with and without altered liver enzymes.…”
Section: Sars-cov-2 and Immune-mediated Collateral Damagementioning
confidence: 99%
“…Nevertheless, only high TBIL levels and NK cell counts were identified by univariable analysis as the only significant risk factors associated with the development of severe pneumonia. 65 Based on the aforementioned evidence, it is very possible that one of the mechanisms contributing to the damage observed in the liver of these patients is related to collateral damage produced by SARS-CoV-2-infected cells which upregulate the inflammasome and produce large amounts of cytokines to help combat the virus. However, this overactivation of the immune system may result in collateral damage to both infected and uninfected host cells stimulated either by the secreted cytokines or by the viral antigens.…”
Section: Sars-cov-2 and Immune-mediated Collateral Damagementioning
confidence: 99%
“…Risk factors for disease severity: Very little is known about this important subject. Radiologic involvement of more than three lung segments carried a higher risk of development of a severe form of the disease 47 . In addition, the elevation of IL‐6, total bilirubin and d ‐dimer are associated with worse disease 47 .…”
Section: Resultsmentioning
confidence: 99%